Cooperation of the Central Asian countries in ensuring regional security - Muratkhan, А.Н.; Abildayev, А.С. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2024)
Central Asia, a region marked by its historical significance and strategic importance, has undergone a remarkable transformation in recent years regarding regional security cooperation. This comprehensive article explores the multifaceted landscape of security cooperation among the five Central Asian nations: Kazakhstan, Kyrgyzstan, Tajikistan, Turkmenistan, and Uzbekistan. It delves into the fundamental concepts of security systems, the role of regional organizations, and the challenges and future prospects of security in the region. Understanding these challenges and exploring future prospects is essential for charting a path toward enhanced stability, cooperation, and prosperity in the region. The article provides a holistic view of the region's security dynamics, beginning with a historical context highlighting Central Asia's role as a crossroads of cultures and interests. It underscores the significance of regional security cooperation in the face of shared challenges and geopolitical complexities. In-depth analyses are conducted on various aspects, including security organizations, diplomatic efforts, regional security challenges, and future prospects. The article explores the complexities and challenges faced by Central Asian nations while navigating a dynamic geopolitical landscape. In conclusion, this article underscores the pivotal importance of cooperation among Central Asian countries and their engagement with regional organizations in maintaining stability and peace.